Leading causes of death for patients admitted to the Al-Sadder teaching hospital since 2006 to June 2012 in Miasn providence / Iraq - Dr. Khalid Obaid Mohsin ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
This study presents data on the major leading causes of death in the Al- Sadder teaching hospital in hospital deaths since 2006 to 2012 by age, sex and the burden of the both communicable and non-communicable diseases . Leading causes of infant mortality , violence and accidents homicide ,burn all were excluded .